2017
DOI: 10.1021/acsbiomaterials.7b00338
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Regenerated Silk Fibroin and Antibody-Containing Microstructures via Multiphoton Lithography

Abstract: Regenerated silk fibroin, a biopolymer derived from silkworm cocoons, is a versatile material that has been widely explored for a number of applications (e.g., drug delivery, tissue repair, biocompatible electronics substrates, and optics) due to its attractive biochemical properties and processability. Here, we report on the free-form printing of silk-based, 3D microstructures through multiphoton lithography. Utilizing multiphoton lithography in conjunction with specific photoinitiator chemistry and postprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 83 publications
(250 reference statements)
1
40
1
Order By: Relevance
“…Additive manufacturing has revolutionized industries, from architecture to aerospace [18][19][20][21][22][23] . The range of materials that can be printed has expanded to include ceramics 24 , metals 25,26 , nylon 27 , silk 28 , cellulose 29,30 , and wood polymer composites 31 . The size of the objects created span from nanometers to houses 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing has revolutionized industries, from architecture to aerospace [18][19][20][21][22][23] . The range of materials that can be printed has expanded to include ceramics 24 , metals 25,26 , nylon 27 , silk 28 , cellulose 29,30 , and wood polymer composites 31 . The size of the objects created span from nanometers to houses 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In their native environment, B. mori spin, via pultrusion, a dual filament fiber composed primarily of the protein fibroin, coated in layers of a secondary protein known as sericin, which acts as a lubricant in the duct and a binder in the cocoon, a non‐woven composite structure . While B. mori's natural fiber mechanical properties are less desirable than those of, say the dragline filaments of Nephila edulis , there is abundant evidence to suggest that they can be further processed to comparable performance levels and their generally more abundant, accessible nature makes them currently a more practical technology platform …”
mentioning
confidence: 99%
“…Due to its biocompatibility, this photo-initiator is widely used in protein photo-crosslinking 67-70 , and is shown to be suitable for light-patterning of reconstituted silk 22 . A key advantage over other photo-initiators is that the riboflavin chromophore absorbs strongly in the violet-blue part of the visible spectrum (between 400-500 nm) 69 , enabling visible light to be used as opposed to previous works where UV light was utilised 16,71 which may result in further damage to the proteins 72,73 .…”
Section: Resultsmentioning
confidence: 99%
“…Moving our attention towards investigating the mechanism behind this structuring process, previous studies have shown that protein solidification in the presence of light and photo crosslinker is usually attributed to chemical crosslinking of the protein 84 . Riboflavin, in particular, has been reported as a suitable photo cross-linker for many natural materials including collagen 67,68,85,86 , alginate 87,88 and silk 22 . Such studies suggest that the key mechanism for riboflavin photo-gelation in silk and other proteins is attributed to the formation of di-tyrosine bonds 22,67,68,86 .…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation